Abweichungsfeste Verfassungsgrundsätze des Unionsrechts als ordre public-Vorbehalt gegenüber dem Völkerrecht - Tamblé, Philipp (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, 2021)
Since the Kadi judgment, the ECJ has repeatedly emphasised that obligations imposed by international agreements cannot have the effect of prejudicing the constitutional principles of Union law. Based on a case law analysis, the study examines these constitutional principles of Union law, which have so far lacked contours. The focus is on the effect of these principles in relation to acts of Union law and international treaties of the Union that are determined by international law. Based on the results, individual constitutional principles are elaborated. A comparison also shows clear similarities of the concept with ordre public exceptions. An outline of the role of constitutional principles in solving current issues rounds off the work.